KEMAMPUAN PENALARAN MATEMATIS SISWA DITINJAU DARI GAYA BELAJAR - Sikky Rokhayah; Khamdun Khamdun; Himmatul Ulya (Jurnal Ilmiah P2M STKIP Siliwangi, 2021)
Grade IV students still need direct directions in solving problems related to complicated questions, it is also seen that when students work on math problems students still look confused or have difficulty determining what is known and asked so that with this students cannot solve or solve a well-given math problem. This study aims (1) to describe students' mathematical reasoning abilities in solving mathematical problems in terms of visual learning styles; (2) to describe students' mathematical reasoning abilities in solving mathematical problems in terms of auditory learning styles; and 3) describe students' mathematical reasoning abilities in solving mathematical problems in terms of kinesthetic learning styles. This study used qualitative methods with research subjects, namely 3 students from grade IV SDN Kropak 02. The data collection techniques in this study used interviews, observation, and document study to analyze the results of students' mathematical reasoning. The results of this study are; (1) Students with a visual learning style are PM. He is able to meet all indicators of mathematical reasoning ability; (2) students with an auditory learning style, namely CA, he fulfills 3 of the 5 indicators of mathematical reasoning; and (3) students with a kinesthetic learning style are RP, they are only able to meet 1 indicator out of 5 indicators of student mathematical reasoning.